TRAINING ON THE CONVERSION TECHNIQUES OF GASOLINE MOTORCYCLES TO ELECTRIC FOR AUTOMOTIVE COMMUNITIES - Fuad Zainuri; Muhammad Todaro; Sonki Prasetya; Muhammad Hidayat Tullah; Rahmat Noval; Muhammad Ridwan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Vehicles powered by gasoline still dominate the roads in Jakarta and its surrounding areas. This has led to uncontrollable levels of pollution in Jakarta. Electric vehicles are one solution to reduce the pollution levels in the city. Since it is not feasible to eliminate all gasoline-powered vehicles to switch to electric vehicles, converting these vehicles into electric ones is a viable solution to address this issue. One of the most widely used gasoline-powered vehicles is the motorcycle. The large number of gasoline motorcycles in Jakarta presents an opportunity for automotive communities, such as conventional vehicle workshops, to participate in the transition to electric vehicles. However, the automotive community must be skilled in converting gasoline motorcycles to electric ones. Training on converting gasoline motorcycles to electric has been conducted for the automotive community in Jakarta. Training participants come from various educational backgrounds, ranging from high school/vocational school to university graduates. As a result, the training participants have been able to increase their knowledge and skills in converting gasoline motorcycles to electric ones by up to 20.54%.